Neoliberalism and after: Scope and limits of interest group representation in public finance decisions - Rajan, Amitabh (2015)
This article begins with a critique of the neoliberal paradigm of governance, situates, and points out the limits and scope of interest-group representation in constitutional democracies post-2008 fiscal crisis experience. Written after an in-depth literature survey of recent research in the sub-disciplines of political economy, the author examines the postulates of the neoliberal framework of policy-advice in public finance decisions from the standpoints of discourse ethics and justice, and recommends structured channelisation of deprivation-consciousness through administrative law reforms. - Reproduced.
Keywords: Public finance; Interest groups; Liberalism